2018
DOI: 10.1007/s00198-018-4639-x
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate therapy in an infant with generalized arterial calcification with an ABCC6 mutation

Abstract: Generalized arterial calcification of infancy (GACI) is a rare genetic disorder with high infantile mortality, described to be due to ENPP1, and less commonly ABCC6 mutations. Bisphosphonate treatment has been described to improve survival in ENPP1-positive GACI patients, but few studies have described bisphosphonate treatment in ABCC6-positive patients. Without therapy, patients will die before 6 months of age. Our patient is now 3 years old, former recipient twin of twin-to-twin transfusion syndrome (TTTS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…summarized 23 cases of prenatal diagnosis, of which 17 were diagnosed at 28 weeks or later, with rare cases diagnosed in the second trimester. The earliest reported prenatal diagnosis of GACI occurred at 19 weeks of gestation 14 . The three cases described in the present report had hyperechogenic valves or annuli as the first presentation during routine sonographic fetal heart screening in the second trimester.…”
Section: Discussionmentioning
confidence: 55%
“…summarized 23 cases of prenatal diagnosis, of which 17 were diagnosed at 28 weeks or later, with rare cases diagnosed in the second trimester. The earliest reported prenatal diagnosis of GACI occurred at 19 weeks of gestation 14 . The three cases described in the present report had hyperechogenic valves or annuli as the first presentation during routine sonographic fetal heart screening in the second trimester.…”
Section: Discussionmentioning
confidence: 55%
“…Historically, calcifications were believed to be mediated by endothelin-1 [2][3][4] ; however, more recent studies have identified pathogenic variants in ABCC6 or ENPP1, which, when found in a compound heterozygous or homozygous state, are known to cause GACI. 5,6 This report is the first to note this phenotype with this variant in the ABCC6 gene and is unique in the finding of a single variant. This case raises multiple possibilities, whether (1) an undetected second pathogenic variant was present; (2) this was an incidental finding; or, (3) the presence of a single variant in ABCC6 is sufficient to cause a phenotype in the appropriate environmental context (increased cardiac myocyte strain and turbulent flow in the great vessels of the recipient twin in TTTS).…”
Section: Discussionmentioning
confidence: 67%
“…The most commonly calcified vessel is the main pulmonary artery, implying a significant right heart strain, which is the dominant side of the heart in utero. Historically, calcifications were believed to be mediated by endothelin‐1 2–4 ; however, more recent studies have identified pathogenic variants in ABCC6 or ENPP1 , which, when found in a compound heterozygous or homozygous state, are known to cause GACI 5,6 …”
Section: Discussionmentioning
confidence: 99%
“…Case reports demonstrate that bisphosphonates and thiosulfates have been successfully used to treat rapid calcification associated with CKD in calciphylaxis patients 239 , 240 and general calcification of infancy. 241 These extreme cases demonstrate the potential of altering mineral formation for therapeutic benefit; however, more studies are needed to determine how to best interact with mineral to reduce cardiovascular risk in the general CKD population. Most studies showing reduced valvular and vascular calcification fail to demonstrate improved cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%